Global Intelligence Priorities (from the Perspective of the United States) - Weaver, John Michael (Political Science and History Ser., 2019)
"The United States is seemingly confronted with more global issues now than it has ever experienced. The U.S., under a relatively new presidential administration, is looking to depart from globalization though there are still inextricable linkages among all countries in the world; in 2018 both the Defense Department and State Department have provided updates to their strategies and security plans. This book provides an open source intelligence analysis of regions, countries and non-state actors from around the world that could have an impact on the United States. These areas and actors are dissected using predominately qualitative analysis techniques focusing on secondary data sources in order to provide an open source intelligence look at threats as seen by the United States using two models (the York Intelligence Red Team Model and the Federal Secondary Data Case Study Triangulation Model). The key audience for this book includes the 17 members of the U.S. intelligence community, members of the U.S. National Security Council, governments of other countries that share the United States' assessment of current threats, nongovernmental organizations (NGOs) looking to provide support abroad, and private sector companies considering expanding their operations overseas"--